Julio Barreiro. Trayectoria intelectual del editor protestante de Paulo Freire - Brugaletta, Federico (2022)
El objetivo de este artículo es describir y analizar la trayectoria de Julio Barreiro (1922-2005) en tanto intelectual protestante de izquierda que se destacó en el campo de la edición, en particular, en el proceso de circulación de la pedagogía de Paulo Freire en el mercado del libro en español. Interesa identificar su itinerario de formación, las redes confesionales y académicas en las que se inscribió y las coyunturas políticas que fueron delimitando su perfil como editor e intelectual.
The objective of this article is to describe and analyse the trajectory of Julio Barreiro (1922-2005) as a Protestant radical left intellectual who stood out in the field of publishing, particularly, in the process of circulation of Paulo Freire's pedagogy in the Spanish book market It is interesting to identify his training itinerary, the confessional and academic networks in which he joined and the political situations that defined his profile as an editor and intellectual.
Keywords: Edición; Protestantismo; Izquierdas; Paulo Freire; Publishing; Protestantism; Political lefts; Recent history; Paulo Freire